High-speed carrier-depletion silicon Mach-Zehnder optical modulators with lateral PN junctions - Reed, Graham T.; Thomson, David J.; Gardes, Frederic Y.; Hu, Youfang; Fedeli, Jean-Marc; Mashanovich, Goran Z. (Frontiers in Physics, 2014)
This paper presents new experimental data from a lateral PN junction silicon Mach-Zehnder optical modulator. Efficiencies in the 1.4 to 1.9 V/cm range are demonstrated for drive voltages between 0 V and 6 V. High speed operation up to 52Gbit/s is also presented. The performance of the device which has its PN junction positioned in the center of the waveguide is then compared to previously reported data from a lateral PN junction device with the junction self-aligned to the edge of the waveguide rib. An improvement in modulation efficiency is demonstrated when the junction is positioned in the center of the waveguide. Finally, we propose schemes for achieving high modulation efficiency whilst retaining self-aligned formation of the PN junction.